Five glutathione s-transferase gene variants in 23,452 cases of lung cancer and 30,397 controls: meta-analysis of 130 studies. - Zheng Ye; Honglin Song; Julian P T Higgins; Paul Pharoah; John Danesh (PLoS Medicine)
Background Glutathione S-transferases (GSTs) are known to abolish or reduce the activities of intracellular enzymes that help detoxify environmental carcinogens, such as those found in tobacco smoke. It has been suggested that polymorphisms in the GST genes are risk factors for lung cancer, but a large number of studies have reported apparently conflicting results. Methods and findings Literature-based meta-analysis was supplemented by tabular data from investigators of all relevant studies of five GST polymorphisms (GSTM1 null, GSTT1 null, I105V, and A114V polymorphisms in the GSTP1 genes, and GSTM3 intron 6 polymorphism) available before August, 2005, with investigation of potential sources of heterogeneity. Included in the present meta-analysis were 130 studies, involving a total of 23,452 lung cancer cases and 30,397 controls. In a combined analysis, the relative risks for lung cancer of the GSTM1 null and GSTT1 null polymorphisms were 1.18 (95% confidence interval [CI]: 1.14-1.23) and 1.09 (95% CI: 1.02-1.16), respectively, but in the larger studies they were only 1.04 (95% CI: 0.95-1.14) and 0.99 (95% CI: 0.86-1.11), respectively. In addition to size of study, ethnic background was a significant source of heterogeneity among studies of the GSTM1 null genotype, with possibly weaker associations in studies of individuals of European continental ancestry. Combined analyses of studies of the 105V, 114V, and GSTM3*B variants showed no significant overall associations with lung cancer, yielding per-allele relative risks of 1.04 (95% CI: 0.99-1.09), 1.15 (95% CI: 0.95-1.39), and 1.05 (95% CI: 0.89-1.23), respectively. Conclusions The risk of lung cancer is not strongly associated with the I105V and A114V polymorphisms in the GSTP1 gene or with GSTM3 intron 6 polymorphism. Given the non-significant associations in the larger studies, the relevance of the weakly positive overall associations with the GSTM1 null and the GSTT1 null polymorphisms is uncertain. As lung cancer has important environmental causes, understanding any genetic contribution to it in general populations will require the conduct of particularly large and comprehensive studies.